Development of Thematic Teaching Materials Integrated with Riau Malay Cultural Values for Grade Elementary Students in Pekanbaru - Erna Nawir; Marhamah Ahmad Hamid; Yulianto; Elpri Darta Putra; Hariri Waldi; Sisi Adelia (UIR Press, 2021)
This study aims to develop thematic teaching materials integrated with Riau Malay cultural values for grade IV elementary students in Pekanbaru by using the Educational Research and Development or Educational R&D method. The development research is carried out in 3 stages, namely: 1) the preliminary study conducted by applying a qualitative descriptive approach by distributing questionnaire and interviewing the teachers and the students in order to find out their actual needs of teaching materials 2) the development of teaching material designed and integrated with the Riau Malay cultural values, followed by expert judgment, revisions, and improvements, limited trials, as well as evaluation and improvement, 3) evaluation which includes the implementation of models created by the quasi- experimental method using the pretest-posttest control group design. The results showed that the research team designed the required teaching material in the second stage in the form of a book entitled ”The 2013 Curriculum Integrated Thematic Supplement,” which can be used by elementary schools in Pekanbaru.